(untitled) (Vietnam Journal of Community Medicine, 2021)
A cross-sectional study was conducted in Tam An hospital, Thanh Hoa province. Our aim described the satisfaction of inpatients on Anus and rectum health-care services. There were 310 patients involved in our study. 209 inpatients (over 310) very satisfied on attitude and capacity of medical staff, with mean score of 4,67/5. On overall, 94,2% of inpatients satisfied with health-care services, and 89% of inpatients would definitely return or refer acquaintances to use services of this hospital. In conclusion, our results showed positive feedbacks of inpatients using Anus and rectum health- care services in terms of access services, facilities and infrastructures, clearance of information and procedures of health care, professional attitude and skills of staff, quality of care in Tam An hospital in 2020.